Comparison of the Efficiency of Two Novel Guided Bone Regeneration Devices in the Rabbit Calvarial Model - Osama Zakaria (The Scientific World Journal)
Background. Creating a secluded large space using guided bone regeneration (GBR) is a novel osteogenesis technique used in the prevention of premature membrane exposure complications. However, this technique is not considered clinically feasible. Objectives. This study aimed to compare the outcome of the insertion of two novel GBR devices in a rabbit calvarial model in terms of mode of action, simplicity, and amount of new space and bone gained. Materials and Methods. The expansible GBR (EGBR) device, composed mainly of a titanium plate, silicone membrane, and activation screw, was inserted beneath the periosteum in the calvarial area of eight rabbits. The smart GBR (SGBR) device, composed of silicone sheets and Nitinol strips, were inserted beneath the periosteum in the calvarial area of another 10 rabbits. Half of each group was sacrificed 2 months after surgery, and the other half was sacrificed after 4 months. Results. Histological and microradiographical analysis showed that, at 2 months, the EGBR device achieved a mean space gain of 207.2 mm3, a mean bone volume of 68.2 mm3, and a mean maximum bone height of 1.9 mm. Values for the same parameters at 4 months were 202.1 mm3, 70.3 mm3, and 1.6 mm, respectively. The SGBR device had significantly higher P<0.05 mean space gain (238.2 mm3; 239.5 mm3), bone volume (112.9 mm3, 107.7 mm3), and bone height (2.7 mm; 2.6 mm) than the EGBR device at 2 and 4 months, respectively. Conclusion. Both devices proved to be effective in augmenting bone vertically through the application of GBR and soft tissue expansion processes. However, the SGBR device was more efficient in terms of mode of action, simplicity, and amount of bone created in the new space.